Reliability based robust control for uncertain dynamical systems using feedback of incomplete noisy response measurements. - Yuen, Ka-Veng (Earthquake engineering & structural dynamics.)
A reliability based output feedback control methodology is presented for controlling the dynamic response of systems that are represented by linear state space models. The design criterion is based on a robust failure probability for the system. This criterion provides robustness for the controlled system by considering a probability distribution over a set of possible system models with a stochastic model of the excitation so that robust performance is expected. The control command signal can be calculated using incomplete response measurements at previous time steps without requiring state estimation. Examples of robust structural control using an active mass driver on a shear building model and on a benchmark structure are presented to illustrate the proposed method.